1963
DOI: 10.2466/pr0.1963.13.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Psychotherapy and Adoption of the Therapist's Meaning System

Abstract: Twelve most improved and 8 least improved clients were used in testing the hypothesis that improvement in therapy is contingent upon the adoption by the client of the personal meaning system of his therapist. The hypothesis was rejected. There was a trend indicating that the most improved client tends to increase in his preference for his own frame of reference, that he tends to become more himself rather than an echo of his therapist. The least improved client tends to internalize the therapist's frame of ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1964
1964
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Moreover, many researchers (e.g., Stanovich & West, 2000) thought cognitive complexity is closely related to general cognitive abilities (e.g., general intelligence). Several studies (Chen & Zhang, 2007;Nawas & Landfiled, 1963) have found positive correlations between academic achievement and cognitive complexity in adults using an instrument similar to the Repgrid. However, no research has been done yet on the relationship between cognitive complexity systematically measured by the Repgrid or the RCQ and academic achievement in adolescents, especially in Chinese adolescents.…”
Section: Controversies Over the Repgrid And Rcqmentioning
confidence: 97%
“…Moreover, many researchers (e.g., Stanovich & West, 2000) thought cognitive complexity is closely related to general cognitive abilities (e.g., general intelligence). Several studies (Chen & Zhang, 2007;Nawas & Landfiled, 1963) have found positive correlations between academic achievement and cognitive complexity in adults using an instrument similar to the Repgrid. However, no research has been done yet on the relationship between cognitive complexity systematically measured by the Repgrid or the RCQ and academic achievement in adolescents, especially in Chinese adolescents.…”
Section: Controversies Over the Repgrid And Rcqmentioning
confidence: 97%
“…Nevertheless, this was the first empirical demonstration of the effects of values in the psychotherapeutic process. Farson ( 1961), Holzman (1961), and Nawas and Landfield (1963) reported findings which were at least partially inconsistent with the phenomenon noted by Rosenthal and by Parloff, et al Farson ( 1961) found Rosenthal's results to be true only when less adjusted and less competent clinicians served as therapists. Schrier reported that improvement was related to the extent to which the patient developed identification with the therapist's need system.…”
Section: Research On Values and Psychotherapy Several Psychologists Hmentioning
confidence: 91%
“…In fact, with inpatients the most improved patients became more different from their therapist in their values. Nawas and Landfield (1963) used G. A. Rosenthal's (1955) pacients were all diagnosed as neurotic and 75% of them were inpatients.…”
Section: Research On Values and Psychotherapy Several Psychologists Hmentioning
confidence: 99%
“…For example, incompatibility of cognitive structure could account for the failure of patients, therapists, and observers to agree about the outcome and nature of the therapy relationship (14,8). Nawas and Landfield (12) hypothesized that most improved patients would show a significant increase from pre to post-therapy in the number of conceptual dimensions borrowed from the therapist, whereas least improved patients should show a decrease. However, the results of their study pointed in the opposite direction, i.e., that improved patients showed a decrease in the number of constructs borrowed from the therapist.…”
mentioning
confidence: 99%